(untitled) (Серія: Історія. Політологія, 2021)
Розглянуто комплекс джерел, який відображає споживання алкогольних напоїв грецьким населенням Маріупольського повіту в ХІХ – на початку ХХ ст. Наявний комплекс письмових джерел класифіковано на актові та діловодні документи, описово-статистичні матеріали та матеріали періодичної преси, джерела особового походження. Надано їх характеристику, історію створення, репрезентативність та інформативні можливості. The studies examine the complex of sources reflecting Mariupol uyezd Greeks alcohol consumption in the XIXth – early XXth centuries. The existing complex of the written sources is classified into stamped (official) and clerical documents, descriptive and statistical materials and periodicals’ materials, sources of special origin. It was determined that the stamped regulatory documents were created due to the existence of the problem of the population’s alcohol abuse and were directed to the minimization of its negative influence by means of prices and fines increase. The stamped sources are representational, most of them are kept in the State Archival Funds of Donetsk region. It was proved that the clerical materials, the doctors’ reports in particular, have the unique data that reflect the scope of alcohol consumption among the Greek villagers and are also complemented with the personal reflections of medical sphere representatives. The descriptive and statistical materials give the significant data concerning quantity of the places where alcohol-containing products were produced, distributed and stored. They also enable to trace the dynamics of their growth; accordingly they represent demand for services in the alcohol beverage market. The article demonstrates that the materials of the city’s newspaper complement the data of the official sources with the “vivid content”, cover the crimes that were committed under the influence of alcohol. They describe the detected crimes, mainly murders and robberies, stepwise that allow tracing peculiarities of the Greek population’s deviant behavior. The sources of special origin concerning the Greeks’ alcohol consumption in their everyday life are represented by travel notes including foreigners’ letters, applications and expeditions’ materials. The article shows that these sources have completely opposite data as to people’s alcohol consumption. It also characterizes the conditions under which they were written and characteristic features of their authors.